2010
DOI: 10.1007/s11274-010-0442-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray

Abstract: In this study, we describe a DNA microarray assay by using bead-mediated visible light-assisted signal detection for simultaneous screening of seven clinically important enteric pathogens, including Escherichia coli O157:H7, Vibrio cholerae, Vibrio parahaemolyticus, Salmonella spp., Staphylococcus aureus, Rotavirus, and Norwalk virus (including genogroup I and II). Seven pairs of primers, in which the forward primers were labeled with biotin at the 5 0 end, were designed and two sets of multiplex asymmetric PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…However, in some instances, an unexpected amplification of genomic DNA was observed using the NASBA technique. The availability of methods for rapid, sensitive, and selective detection of viable microbial pathogens in foods is a goal worth pursuing, and a developmental effort to explore and capitalize on NASBA’s potential in this regard could be worthwhile [ 45 ].…”
Section: Isothermal Amplificationmentioning
confidence: 99%
“…However, in some instances, an unexpected amplification of genomic DNA was observed using the NASBA technique. The availability of methods for rapid, sensitive, and selective detection of viable microbial pathogens in foods is a goal worth pursuing, and a developmental effort to explore and capitalize on NASBA’s potential in this regard could be worthwhile [ 45 ].…”
Section: Isothermal Amplificationmentioning
confidence: 99%
“…This assay was validated with 1500 diarrheal stool samples and 200 samples from healthy individuals and showed a sensitivity of 100% and specificity of 95.2% with an LOD of 10 3 cfu/ml. A magnetic bead-based DNA microarray test for the simultaneous screening of five enteric bacteria and two viruses, which can be read out by the naked eye or a digital camera, was developed by Sun et al [33]. The microarray detection was combined with two sets of asymmetric multiplex PCR systems.…”
Section: Infectious Diarrheamentioning
confidence: 99%
“…The HCII assay is based on hybridization in a solution with a mixture of nonisotopic, single-stranded, full-length RNA probes against 13 high-risk types (HPV 16,18,31,33,35,39,45,51,52,56,58,59,68). The assay detects several high-risk types in one reaction and uses a convenient format.…”
Section: Commercial Hpv Testsmentioning
confidence: 99%
“…Several functions of repeated sequences in MYCOPLASMA genomes have been highlighted in some studies (Ruland et al, 1990;Himmelreich et al, 1996;Himmelreich et al, 1997;Altshuler et al, 2000;Chambaud et al, 2001;Jaffe et al, 2004;Minion et al, 2004;Mrázek, 2006;Kassai-Jáger et al, 2008;Ma et al, 2008;Ma et al, 2012). DNA sequence repeats have also been found in enteric pathogens that are responsible for bacillary dysentery in humans (Jin et al, 2002;Wei et al, 2003;Yang et al, 2003;Phalipon and Sansonetti, 2007;Saurabh et al, 2011;Sun et al, 2011). Other studies have also revealed the significance of conducting comparative analyses and repeats in the genomes of various organisms (Powell et al, 1996;Chen et al, 2003;Ju et al, 2005;Rahim, 2008;Shikano et al, 2010;Labbe et al, 2011;Saker et al, 2011;Tyagi et al, 2011).…”
Section: Multifaceted Applications Of Repeat Analysismentioning
confidence: 99%